2020
DOI: 10.1111/jvs.12894
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal syndrome influences the match between seed rain and soil seed bank of woody species in a Neotropical dry forest

Abstract: Aims Plant recruitment may occur immediately after seed dispersal from the mother plant, or be delayed through the formation of soil seed banks. These strategies are known to be mediated by adaptations of seed dispersal and reproductive phenology, which if analyzed together can provide valuable information about the regeneration strategies of species. We explored whether dispersal syndrome and/or seed dispersal phenology control the similarity between standing vegetation, seed rain and soil seed bank in a seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 78 publications
0
14
0
4
Order By: Relevance
“…It is common to consider dispersal separately from other processes governing the establishment, but these processes are intrinsically linked, as Korablev et al (2020, this issue) and Anadon‐Rosell et al, 2020, this issue) showed. Jara‐Guerrero et al (2020, this issue) demonstrated a functional link between dispersal syndrome, establishment and seed banking in Ecuadorian dry forest. Animal‐dispersed species are dispersed in the rainy season and likely germinate immediately, whereas wind‐dispersed species do so in the dry season and become incorporated into the seed bank.…”
Section: Dispersal In Spacementioning
confidence: 99%
See 1 more Smart Citation
“…It is common to consider dispersal separately from other processes governing the establishment, but these processes are intrinsically linked, as Korablev et al (2020, this issue) and Anadon‐Rosell et al, 2020, this issue) showed. Jara‐Guerrero et al (2020, this issue) demonstrated a functional link between dispersal syndrome, establishment and seed banking in Ecuadorian dry forest. Animal‐dispersed species are dispersed in the rainy season and likely germinate immediately, whereas wind‐dispersed species do so in the dry season and become incorporated into the seed bank.…”
Section: Dispersal In Spacementioning
confidence: 99%
“…A long‐standing method has been to assign species to different dispersal syndromes such as by wind, animals, water or unaided (autochory). These syndromes do capture species differences in dispersal distance and can be used to explain vegetation patterns (Jara‐Guerrero et al, 2020, this issue; Korablev et al, 2020, this issue). But there is a great deal of interspecific variation in dispersal abilities within syndromes, due to the exact vector and its behaviour, plant characteristics such as height, and seed traits such as mass (Tamme et al, 2014; Bullock et al, 2017).…”
Section: Dispersal In Spacementioning
confidence: 99%
“…Por otro lado, se han relacionado características funcionales de las especies con la formación de bancos de semillas como son la forma de vida, tamaño y forma de las semillas, tipo de testa, fenología, etc. (Christian y Stanton 2004, Couvreur et al 2005, Valenta et al 2015, Metzner et al 2017, Jara-Guerrero et al 2020. En algunos estudios han encontrado que las especies que no forman parte de los bancos de semillas dependen de su capacidad de dispersarse en el espacio, mientras que las especies con dispersión a corta distancia, al parecer, son las que persisten más en el banco y su dispersión es en el tiempo (von Blanckenhagen y Poschlod 2005).…”
Section: Dinámica De La Lluvia Y Banco De Semillasunclassified
“…O banco de sementes do solo é constituído pela existência de sementes e outros propágulos que se encontram sobre a camada superficial ou no interior do solo, viáveis ou dormentes, recrutadas através da chuva de sementes proveniente de espécies da própria área ou áreas adjacentes (MARTINS et al, 2015;JARA-GUERRERO et al, 2020). Consiste em um sistema dinâmico que apresenta entradas pela dispersão das espécies, e saídas que ocorrem devido à predação (aves, roedores), perda de viabilidade e morte das sementes, bem como pela germinação (CALDATO et al, 1996;MIRANDA-NETO et al, 2014).…”
Section: Introductionunclassified
“…Análise de dadosOs parâmetros fitossociológicos de densidade, frequência e valor de importância(MUELLER-DOMBOIS & ELLENBERG, 1974), bem como os índices de diversidade de Shannon(MAGURRAN, 1988) e de equabilidade(PIELOU, 1975) foram calculados para cada área utilizando o programaFITOPAC 2.1 (SHEPHERD, 2010). Foi construído um diagrama de Veen para avaliar a similaridade de acordo com o número de espécies compartilhadas entre as áreas.de presença/ausência e número de Hill de ordem 0 com 999 replicações de bootstrap para estimar intervalos de confiança de 95% dos valores observados e estimados(COLWELL et al 2012), usando o pacote "iNEXT"(HSIEH et al 2016). Sempre que os intervalos de confiança lias botânicas.…”
unclassified